[On the right track-LRT ; It's time ; Police bill [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Tackles Light Rail Transit as a solution to the lack of public transportation; interview with L. Reyes about her jazz singing; and the controversial issue of the abolition of the Philippine Constabulary.
On the right track-LRT (16 min.) -- It's time (11 min.) -- Police bill (15 min.)
VHS.
Keywords: Reyes, Louie; Philippine Constabulary; Philippine National Police; Railroads, Local and light -- Philippines; Jazz singers -- Philippines; Police -- Philippines